Experimental Study and Numerical Simulation on Failure Process of Reinforced Concrete Box Culvert - Yafeng Gong; Yulin Ma; Guojin Tan; Haipeng Bi; Yunze Pang; Chen Ma (Advances in Civil Engineering)
Culvert is an important part of roads whose healthy operation is related to the efficiency and safety of road transportation. Therefore, it is very important to evaluate the safety of culvert structure by load test. Four types of prefabricated reinforced concrete box culverts (integral BC, round hinged BC, flat seam BC, and mortise BC) were designed in this paper. By designing a scale model test, the sensor system was used to test the mechanical properties of BC, which included dial indicators, strain gauges, and a pressure sensor. The finite element analysis based on material nonlinearity and contact nonlinearity of round hinged BC and integral BC was carried out. After validating the finite element models, mechanical properties of reinforcement and concrete of BCs were analyzed. The experimental results show that the failure mode of BC was tensile failure of concrete at the bottom of top slab under bending action, and integral BC had the maximum carrying capacity. The contact behaviour of sliding and rotating at hinge joints caused the first principal tensile stress of concrete at the internal surface of the side wall below hinge joints.